Hubungan Waiting Time Dan Length Of Stay dengan Kepuasan Pasien di Ruangan Intalasi Gawat Darurat di RSU GMIM Pancaran Kasih Manado - Gina Maria Rosalinda Haringan; Rahmat Hidayat Djalil; Suwandi I. Luneto (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Quality of time is important and effected of patient satisfaction in the emergency room to see the level of density and clinical performance, waiting time and length of stay (LOS) were used. In the emergency room, LOS are often encountered, this can affect patient satisfaction. The aim of this research was to determine the relationship between waiting time and LOS with patient satisfaction in the emergency room at RSU GMIM Pancaran Kasih Manado. The research was conducted using descriptive analytical research methods. The sample in this study was 42 respondents taken by accidental sampling with research instrument using observation sheets, stopwatches and questionnaires. Next, the data collected processed using the SPSS version 16.0 computer program to be analyzed by Chi-square test with a significance level (a) of 0.05. The results of this study showed the relationship between waiting time and patient satisfaction in the emergency room, with a value of p = 0.000, which is 0.000, which is smaller than the value of a = 0.05. It can be said that Ha is accepted and HO is rejected and it can be concluded that Ha is a waiting relationship time with patient satisfaction in the ER. The results in the LOS study obtained a value = 0.000, this p value was smaller than the a value = 0.05, it was concluded there was a relationship between LOS and patient satisfaction in the ER.The conclusion in this research is the waiting time and length of stay on patient satisfaction emergency installation room at RSU GMIM Pancaran Kasih Manado was.. There is a LOS relationship with patient satisfaction in the emergency room at RSU GMIM Pancaran Kasih Manado. It is hoped and suggestions to improve the quality of service time in the ER to obtain the patient satisfaction